The triglyceride-glucose index is associated with coronary plaque features and clinical outcomes in patients with ST-segment elevation myocardial infarction - Guo, Yibo; Cui, Lina; Guo, Jiaqing; Jin, Chengmei; Xiu, Lili; Gao, Yubo; Zhao, Chen; Xu, Xueming; Tan, Jinfeng; Han, Jincheng; Li, Lulu; Chen, Tao; et al. (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose (TyG) index is a reliable surrogate marker for insulin resistance, and is associated with cardiovascular diseases. However, the specific impact of TyG index on coronary plaque vulnerability and long-term outcomes in patients with ST-segment elevation myocardial infarction (STEMI) has not been fully investigated. This study aimed to investigate the association of the TyG index with coronary plaque characteristics and clinical outcomes.MethodsBetween January 2017 to December 2019, 1,831 STEMI patients who underwent optical coherence tomography imaging were retrospectively enrolled. Patients were divided into three groups based on TyG index tertiles (Group T1: <8.82, Group T2: 8.82-9.41, Group T3: ≥9.41). Major adverse cardiovascular and cerebrovascular events (MACCE) included cardiac death, non-fatal stroke, non-fatal myocardial infarction, ischemia-driven revascularization, and rehospitalization.ResultsThe average age was 58.7 years, and 72.1% were male. The incidence of plaque rupture, thin-cap fibroatheromas, macrophages, and the size of lipid core, increased with increasing TyG index tertiles (all P<0.05). Multivariate logistic regression analysis showed that TyG index independently predicted culprit plaque rupture (T2: OR 1.39, 95%CI 1.06-1.82; T3: OR 1.51, 95%CI 1.05-2.16; T1 as reference). During a median follow-up of 4.2 years, 541 (29.9%) patients developed MACCE. Patients in the highest TyG index tertile had a significantly higher cumulative incidence of MACCE (43.5% vs. 37.3% vs. 31.1%, P = 0.007) than the other two groups. After adjusting for clinical risk factors and coronary plaque features, the increased TyG index independently predicted MACCE (HR 1.18, 95%CI 1.00-1.38, per unit increased). This association was notable in patients without diabetes but was not demonstrable in diabetes (interaction P-value <0.05).ConclusionsIn patients with STEMI, elevated TyG index increased atherosclerotic plaque vulnerability, and independently predicted plaque rupture. A higher TyG index was an independent predictor of MACCE, especially for patients without diabetes.